Improving the visibility of the institution, researchers, and publications by introducing specific identifiers (PIDs) (Journal of EAHIL, 2023)
In the course of 2021, the Belgian Health Care Knowledge Centre (KCE) has decided to give further thought to improving the visibility of these publications. This has led it to develop a project to set up three types of PIDs - one for the institution, another for researchers and the third for the publications themselves. The purpose of this text is to retrace the various stages in the project's implementation and to share the initial findings.